THE GLOBALIZATION STRATEGY OF VIETNAMESE IT ENTERPRISES IN THE CONTEXT OF ASEAN ECONOMIC COMMUNITY VIA THE CASE STUDY OF FPT CORPORATION HOANG VAN CUONG, (DIRECTOR OF INTERNATIONAL MOBILITY DEPARTMENT, FPT UNIVERSITY VIETNAM) - Hoang Van Cuong (Proceeding International Conference on Information Technology and Business, 2015)
Vietnam IT Industry has been growing rapidly duringthe past 15 years. It has been considered as the mainshort cut to develop the Vietnamese economy from a lowincome to a middle income country (MIC). From 2002to 2013, the revenue of software industry increased 52times to reach nearly 3 US billion; and the revenue ofhardware industry increased 70.5 times to reach 36.8US billion. Hanoi and Ho Chi Minh City – the twobiggest cities in Vietnam have been ranked in the Top100 outsourcing destinations by Tholons (an advisoryfirm for global outsourcing and investment).ASEAN is one of the key markets for Vietnam’sIT industry. The region also provides a high potentiallabor force market to solve the human resourceproblems of the IT enterprises. In this context, ASEANEconomic Community will have a significant influenceto the development of Vietnam’s IT enterprises.This paper will discuss the globalizationstrategy of Vietnamese IT enterprises in the context ofASEAN Economic community via the case of FPTCorporation – the leading IT Company in Vietnamwhich currently has its office in Singapore, Malaysia,Thailand, Laos, Cambodia, Myanmar, Indonesia andthe Philippines.